The index construction of cross-media concentration in the digital era: A comparative study - Kuo-Feng Tseng (International Telecommunications Society (ITS), 2014)
In the convergence age of media, telecommunication and Internet, firms need more media contents, audiences or platforms to acquire the economics of scale or scope. Some critics argued that the traditional antitrust law handles the violation of horizontal and vertical merger & acquisition, but not for the conglomeration. If the conglomerate's shares are small in each individual market, whether the sum of the total shares will deter new competitors from entering the market requires further discussion. The KEK, the index of cross-media concentration used in German, is applied to examine the degree of multiple market concentration. However, this study found that for most countries they did not analyzed M&A cases by using the similar KEK index because there are many questions raised in the calculation and definition. Currently the antitrust law is practicable enough to keep the cross media competitive if the barrier could be removed and new entry could enter the market.
Keywords: 330; merger; acquisition; conglomerate; concentration; cross media; antitrust law